2016
DOI: 10.1590/0001-3765201520140374
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and anti-inflammatory effects of a Geissospermum vellosii stem bark fraction

Abstract: Geissospermum vellosii (Pao pereira) is a Brazilian tree whose stem barks are rich in indole alkaloids that present intense anticholinesterase activity. The present study evaluated the effects of a stem bark fraction (PPAC fraction) and ethanolic extract (EE) of Pao pereira in classic murine models of infl ammation and pain. The EE and PPAC fraction, both at a dose of 30 mg/kg, signifi cantly reduced mice abdominal constriction induced by acetic acid by 34.8% and 47.5%, respectively. In the formalin test, EE (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 73 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Pao extract, derived from bark of Amazonian tree Pao Pereira, is commonly used in South American medicine to treat a variety of ailments including cancer 23,24 . We and others have reported that Pao extract can inhibit human prostate cancer cell proliferation and survival in vitro and in vivo 25,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pao extract, derived from bark of Amazonian tree Pao Pereira, is commonly used in South American medicine to treat a variety of ailments including cancer 23,24 . We and others have reported that Pao extract can inhibit human prostate cancer cell proliferation and survival in vitro and in vivo 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Pao pereira extract is an herbal extract derived from the bark of the Amazon rainforest tree, Geissospermum vellosii , that has been used historically as a medicine by South American Indian tribes. The bark of Pao pereira shows anti-plasmodial, antinociceptive and anti-inflammatory activities 23,24 . Recent studies revealed that a β-carboline alkaloid-enriched Pao extract has inhibitory effects on two prostate cancer lines, LNCaP and PC3 by inhibiting cell proliferation and survival 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous infusions of its bark are frequently used by native societies for countless medicinal determinations. It is medically significant plant and exerts a round figure of medicinal potentials as anti-oxidant 109 as well as antibacterial and antimalarial 110 , 111 .…”
Section: Geissosperminementioning
confidence: 99%
“…Studies with isolated indole alkaloids, extracts and fractions of different parts of Geissospermum spp. have reported antitumor pharmacological (Bastos, 2017;Bemis et al, 2009;Chang et al, 2014;Liu et al, 2019;Sajkowska-Kozielewicz et al, 2016;Yeh et al, 2019;Yu and Chen, 2014), antinociceptive, anti-inflammatory (Lima et al, 2016;Werner et al, 2009), anticholinesterase (Araújo et al, 2011;Lima et al, 2020Lima et al, , 2009, antileishmania, antitrypanosoma(da Silva e Silva et al, 2019;Reina et al, 2012), anti-HIV (Beljanski, 2005), antimicrobial (Camargo, 2011;Correia et al, 2008;Dias, 2012;Saraiva, 2012), cardiovascular (Martins, 2010;Morais, 2012), antioxidant (Sajkowska-Kozielewicz et al, 2016), andantimalarial (Bertania et al, 2005;Camargo, 2011;Mbeunkui et al, 2012;Muñoz et al, 2000;Oliveira, 2018;Steele et al, 2002). This review aims to update the ethnopharmacology, the phytochemistry and the biological activities of Geissospermum species described in the literature in order to contribute to the knowledge of bioactive compounds of therapeutic interest and establish directions for future research with this genus.…”
Section: Introductionmentioning
confidence: 99%